Current status of emergency airway management for elderly patients in Korea: Multicentre study using the Korean Emergency Airway Management Registry. (9th September 2013) - Cho, Junho; Cho, Young Soon; You, Je Sung; Lee, Hye Sun; Kim, Hyunjong; Chung, Hyun Soo; ,
Abstract Objective We report the current status of emergency airway management in elderly Korean patients by analysing a multicentre registry database in order to provide quality emergency airway management to elderly patients. Methods The present study was designed as a retrospective, subgroup analysis of the registry of Korean Emergency Airway Management Society. We analysed rapid sequence intubation rate, first pass success rate and complications. Results The study consisted of 4891 patients aged 65 years and older. The anticipation rate of difficult airway for age younger than 65 years, age 65 years and older and age 80 years and older was 15.8% (805/5090; 95% confidence interval [CI], 14.8–16.8), 12.0% (376/3146; 95% CI, 10.9–13.1) and 8.5% (97/1140; 95% CI, 7.0–10.0) respectively (P < 0.001). Rapid sequence intubation was performed on 27.8% (1683/6051; 95% CI, 26.7–29.0) of the patients aged younger than 65 years, 26.5% (954/3599; 95% CI, 25.1–28.0) of the patients aged between 65 and 79 years and 25.2% (325/1292; 95% CI, 22.8–27.6) of the patients aged 80 years and older (P = 0.097). First pass success was shown in 4837 (79.9%; 95% CI, 78.9–80.9) of 6051 patients aged less than 65 years, 2868 (79.7%; 95% CI, 78.3–81.0) of 3599 patients aged between 65 and 79 years and 1069 (82.7%; 95% CI, 80.5–84.7) of 1292 patients aged 80 years and older (P = 0.047). No differences were found between each group in the comparison of complication incidence by age (P = 0.686). Conclusions Similar success and complication rates were found for emergency airway management in elderly patients compared with patients aged less than 65 years.